2007
DOI: 10.1111/j.1525-1594.2007.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Circulation, Optimized: A Pilot Study

Abstract: We designed a pilot study to assess as primary end point the safety and efficacy of a new phosphorylcholine-coated, closed cardiopulmonary bypass (CPB) system (extracorporeal circulation, optimized [ECC.O], Dideco, Mirandola, Italy). The secondary end point was to compare results with two retrospectively matched cohorts of patients who underwent isolated coronary artery by-pass graft (CAGB) with nonphosphorylcholine-bonded circuits and cardiotomy suction (Group II, n = 32) and off-pump coronary artery by-pass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…To reduce the amount of transfused RBCs in cardiac surgery there are many techniques and approaches, one of them is reducing the priming volume with an intended result of diminishing hemodilution. 1,2,11,13,14 This must affect the hematocrit values during CPB and reduce or obviate the need for transfusion of RBCs. Over a period of three years, we minimized our CPB circuit by the introduction of integrated components and optimizing the circuit with a better configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the amount of transfused RBCs in cardiac surgery there are many techniques and approaches, one of them is reducing the priming volume with an intended result of diminishing hemodilution. 1,2,11,13,14 This must affect the hematocrit values during CPB and reduce or obviate the need for transfusion of RBCs. Over a period of three years, we minimized our CPB circuit by the introduction of integrated components and optimizing the circuit with a better configuration.…”
Section: Discussionmentioning
confidence: 99%
“…These systems need a different approach of operation technique and a team that is familiar with this equipment. 11,12 These techniques were beyond the scope of this retrospective audit. Until 2010, the CPB circuit in our institution consisted of an oxygenator with a separate arterial filter.…”
Section: Introductionmentioning
confidence: 99%
“…It can be utilized to automatically close the arterial line and prevent the device from depriming in case of massive air introduction. The ERC will close automatically also if retrograde fl ow is detected, preventing reverse fl ow through the system [ 77,78 ] .…”
Section: Ecco (Sorin)mentioning
confidence: 99%
“…Salvator Agati et al. (48) of the San Vincenzo Hospital (Messina, Italy) reported on their design of a pilot study to assess the safety and efficacy of a new phosphorylcholine‐coated, closed CPB system. The secondary end point was to compare results with two retrospectively matched cohorts of patients who underwent isolated coronary artery by‐pass graft (CABG) with nonphosphorylcholine‐bonded circuits and cardiotomy suction (Group II, n = 32) and off‐pump coronary artery by‐pass (Group III, n = 26).…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%
“…Salvator Agati et al (48) of the San Vincenzo Hospital (Messina, Italy) reported on their design of a P.S. MALCHESKY 246 pilot study to assess the safety and efficacy of a new phosphorylcholine-coated, closed CPB system.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%